Penggunaan Media Permainan Congklak dalam Pembelajaran Matematika Materi KPK di Kelas IV - Abdurrohman, Aji Madia (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
According to Trianto, one of the main problems in learning mathematics in schools today is the low absorption of students. The way that can be used to overcome these problems is by using media in learning mathematics. From the results of writing conducted by Luh Made Suriwati, et al, it was found that learning with the help of visual media is more effective in improving student learning outcomes compared to conventional learning methods. One of the media that can be used in learning mathematics is Congklak game media.This type of writing is action research aimed at developing an action plan to improve what is being done now. This writing is descriptive writing, where this writing is writing that really only describes what is contained or occurs in a particular scene, field, or region, namely SD N 1 Toyareka. This writing uses data collection techniques in the form of interviews, observation and documentation while the technical analysis of data uses data reduction, data presentation and data conclusion. The purpose of this writing is to describe the use of Congklak game media in learning mathematics in class IV and the use of Congklak game resources in instilling student character.The results of the writing show that the Congklak media can be used in learning Mathematics of Multiples Small Guilds. Where in the use of the media, the authors modify the game board by giving writing numbers in each hole of the board. Through the use of these media students can actively and enthusiastically participate in chases that have an impact on improving student learning outcomes. In addition, through the use of the Congklak game media can help teachers to convey the concept of Multiple Small Guilds (KPK) easily and at the same time be more acceptable to students. Through the use of congklak game media can also instill the character of students' curiosity.